2014
DOI: 10.5194/nhess-14-2829-2014
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and applications of WRF–SFIRE

Abstract: Abstract. Coupled atmosphere-fire models can now generate forecasts in real time, owing to recent advances in computational capabilities. WRF-SFIRE consists of the Weather Research and Forecasting (WRF) model coupled with the fire-spread model SFIRE. This paper presents new developments, which were introduced as a response to the needs of the community interested in operational testing of WRF-SFIRE. These developments include a fuel-moisture model and a fuel-moisture-data-assimilation system based on the Remot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 39 publications
1
79
0
Order By: Relevance
“…WRF-SFIRE [22,23] evolved from CAWFE [24,25] and it has been a part of WRF since release 3.2 as WRF-Fire [23,26]. After release 3.3, WRF-SFIRE has continued to develop outside of WRF release [1,12]. The version in WRF release was recently selected as a foundation of the operational Colorado Fire Prediction System (CO-FPS) [27] and the level set method was improved [28].…”
Section: Coupled Atmosphere-fire Simulationmentioning
confidence: 99%
See 3 more Smart Citations
“…WRF-SFIRE [22,23] evolved from CAWFE [24,25] and it has been a part of WRF since release 3.2 as WRF-Fire [23,26]. After release 3.3, WRF-SFIRE has continued to develop outside of WRF release [1,12]. The version in WRF release was recently selected as a foundation of the operational Colorado Fire Prediction System (CO-FPS) [27] and the level set method was improved [28].…”
Section: Coupled Atmosphere-fire Simulationmentioning
confidence: 99%
“…Therefore, characterizing fire-atmosphere interactions, including wildland fire behavior and plume dynamics, is fundamental for improving estimates of smoke production and dispersion. The proposed observational data to be collected during the Fire and Smoke Model Evaluation Experiment (FASMEE) [9,10] are critical for evaluating and transitioning coupled fire-atmosphere models like WRF-SFIRE and WRF-SFIRE-CHEM [1,11,12] into operational use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these are restricted to research use, and small-and particular-scale applications owing to the high computational costs and initialising data required (Viegas 2011). A simplified version of a CFD model that couples weather modelling with Rothermel's fire-spread model (Rothermel 1972) named WRF-SFIRE (Mandel et al 2014(Mandel et al , 2011 was recently reported to have been applied operationally, as a 6-h forecast could be launched with a 30-min run in a multicore processor. Cruz and Alexander (2013) reviewed 49 fire spread models datasets and found that only 3% of the simulations acceptably predicted the observed rate of spread (RoS) and revealed the need to adjust those models if they were to be used operationally.…”
Section: Introductionmentioning
confidence: 99%